2018
DOI: 10.1177/1934578x1801300908
|View full text |Cite
|
Sign up to set email alerts
|

Constituents of the Rhizomes of Sansevieria cylindrica

Abstract: A new sappanin-type 3-benzyl chroman-4-one (homoisoflavanone), (3S)-3-(4′-methoxybenzyl)-3,5-dihydroxy-7-methoxy-6-methyl chroman-4-one (1), together with known congeners (3S)-3-(4′-methoxybenzyl)-3,5-dihydroxy-7-methoxy chroman-4-one (2), (3S)-3-(4′-hydroxybenzyl)-3,5-dihydroxy-7methoxy-6-methyl chroman-4-one (3), (3S)-3-(4′-hydroxybenzyl)-3,5-dihydroxy-7-methoxy chroman-4-one (4), 3-(3',4'-methyledioxybenzyl)-7-hydroxy-8methoxy chroman-4-one (5), and stigmasterol and ergosterol peroxide have been isolated fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 17 publications
(26 reference statements)
0
13
0
Order By: Relevance
“…The residue E from the EtOAc subextract of the MeOH extract of S. cylindrica rhizomes was subjected to flash column chromatography over octadecylsilanized silica gel (ODS) followed by repeated semipreparative HPLC separations to afford ten known compounds (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). The physical and spectroscopic data of 1-10 nicely matched those reported in the literature.…”
Section: Resultsmentioning
confidence: 60%
See 4 more Smart Citations
“…The residue E from the EtOAc subextract of the MeOH extract of S. cylindrica rhizomes was subjected to flash column chromatography over octadecylsilanized silica gel (ODS) followed by repeated semipreparative HPLC separations to afford ten known compounds (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). The physical and spectroscopic data of 1-10 nicely matched those reported in the literature.…”
Section: Resultsmentioning
confidence: 60%
“…While browsing literature reports, we found that a compound isolated from S. roxburghiana [22] was claimed to have the same structure as ()-cambodianol (2), isolated from Dracaena cambodiana [10]. However, upon carefully examining the 13 C NMR resonances determined for the homoisoflavanone from S. roxburghiana [22], we found that they were similar to the 13 C NMR signals of homoisoflavanone 11, which was previously isolated from Liriope muscari [23] and S. cylindrica [8]. In contrast, the 13 C NMR data of the compound isolated from S. roxburghiana [22] were significantly different from those determined for cambodianol (2) [10], although the solvents were not the same.…”
Section: Resultsmentioning
confidence: 64%
See 3 more Smart Citations